2020
DOI: 10.3390/su12197844
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Society for Automated Vehicles: Perceptions of the Importance and Urgency of Emerging Issues of Governance, Regulations, and Wider Impacts

Abstract: This study explores the overall picture of how people perceive the importance level and urgency level regarding issues associated with automated vehicles, by sorting out ten issues, developing a questionnaire with 66 measurement items, and investigating how Artificial Intelligence (AI) experts and Computer Science (CS)/Electrical Engineering (EE) majors assessed these issues. The findings suggest that AI experts in Taiwan believed that the top five issues for preparing a society for autonomous vehicles (AVs) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The blackbox nature of the decisions taken by AIs without much transparency (which, at times, are wrong), the possibility of AI failing in a life-or-death context, and cybersecurity vulnerabilities all limit public trust. AI technology needs to earn the trust not only in the public and the way people perceive it, but also in the minds of companies and government agencies that will be investing in AI [182][183][184]. This is a challenging problem because, as Greenfield [121] notes, AI is an arcane technology meaning that, although it is already part of the everyday of many people, its mechanics and actual functioning are understood by only a few.…”
Section: Discussion: Better Artificial Intelligence For Better Citiesmentioning
confidence: 99%
“…The blackbox nature of the decisions taken by AIs without much transparency (which, at times, are wrong), the possibility of AI failing in a life-or-death context, and cybersecurity vulnerabilities all limit public trust. AI technology needs to earn the trust not only in the public and the way people perceive it, but also in the minds of companies and government agencies that will be investing in AI [182][183][184]. This is a challenging problem because, as Greenfield [121] notes, AI is an arcane technology meaning that, although it is already part of the everyday of many people, its mechanics and actual functioning are understood by only a few.…”
Section: Discussion: Better Artificial Intelligence For Better Citiesmentioning
confidence: 99%
“…Considering that AVs collect extensive data about users and their travel patterns, the degree to which regulations safeguard user privacy will determine how widely AVs are adopted 38 . The authors 7 found that regulation was one of the significant negative predictors of the urgency level of AV development in Taiwan. Therefore, to examine the impact of demographic factors on the lack of AV cybersecurity regulation, it is hypothesised that:…”
Section: Dimensions Of the Av Cyber Barriersmentioning
confidence: 98%
“…However, the pace of ITS infrastructure is significantly slower than that of AV technology, which is also a cause for anxiety. Infrastructure was identified as one of the significant positive predictors of the urgency level of AV deployment in Taiwan 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Policymakers have so far focused on enabling pilots, while countries and cities have increasingly incorporated SDVs into their plans and visions [33]. Simultaneously, a growing body of academic literature has begun to examine the questions of transport policy and governance concerning the uncertain aspects of the emerging technology (see, for example, [1,3,6,7,23,25,[33][34][35][36][37][38][39][40][41][42][43]). This research has come to a few interconnected and troubling conclusions:…”
Section: Critical Literature On the Governance Of Self-driving Vehicl...mentioning
confidence: 99%